The Learning of Toraja Language Variations: The Students' Attitudes, Attendance, Activity Change, and Learning outcomes in Ke'te' Kesu' Toraja Tourism Site Context - Shilfani, Shilfani; Taula’bi’, Nilma; Sudarsi, Elim Trika; Girik Allo, Markus Deli; Kristanto, Kristanto (Jurnal Pendidikan Indonesia, 2022)
This study aims at investigating on how students' attitudes, attendance, and activity change in the learning of Toraja language variations for elementary school students and describe the results of students learning the Toraja language variations in elementary school students. In this study, researchers applied mixed-method. The Research design applied for qualitative is descriptive qualitative and for quantitatively applied pseudo-experiment. The respondents to this study were elementary school students. The research sample selection technique used is purposive sampling. The techniques for analyzing data used in this study are thematic analysis and statistic techniques. In qualitative data analysis, researchers applied thematic analysis techniques, and in quantitative data, researchers tabulated the data, then calculated the average scores, then described the criteria and categories of student learning outcomes. This study showed that In general, the results achieved by students after the implementation of the learning process of teaching Variations of Toraja Language in elementary school children in Ke'te' Kesu' Toraja tourism location could provide improvement both from changing student attitudes, activeness, attention, and motivation in completing tasks. Student learning results on learning variations of Toraja language in elementary school students at Ke'te' Kesu' Toraja tourism location is a good category, as evidenced by an average score of 74.16In applied linguistics, this study provides new vocabulary related to social context. In literary works, this study provides local oral literature as the insight for the students to broaden their knowledge.